2022
DOI: 10.1002/aoc.6889
|View full text |Cite
|
Sign up to set email alerts
|

Novel Schiff base transition metal complexes for imparting UV protecting and antibacterial cellulose fabric: Experimental and computational investigations

Abstract: In the search for ultraviolet radiation exposure protective textile to minimize risk factors for skin cancer, we synthesized a Schiff base ligand from the condensation reaction 2,4‐dihyroxybenzaldehyde with p‐amino aniline. Also, the Schiff base complexes with Fe (III), Mn (II), and Cr (III) were synthesized. The ligand and the complexes were characterized by ultraviolet (UV)‐visible, Fourier transform infrared spectroscopy, 1H 13C NMR, X‐ray diffraction, and elemental analysis. We treated cotton fabric (CF) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…It showed that Cr(III), Mn(II), and Fe(III) complexes had higher inhibition zone diameters than Saeed's complexes. These results encouraged us that our synthesized complexes gave good activities and hence the possibilities of further studies as antimicrobial drugs 52 …”
Section: Resultssupporting
confidence: 58%
“…It showed that Cr(III), Mn(II), and Fe(III) complexes had higher inhibition zone diameters than Saeed's complexes. These results encouraged us that our synthesized complexes gave good activities and hence the possibilities of further studies as antimicrobial drugs 52 …”
Section: Resultssupporting
confidence: 58%
“…The electronic spectrum of the Schiff base established a strong band at 370 nm, which can be related to n‐π* transition of the azomethine group. This band shifted in all complexes to lower wavenumber indicating its participation in coordination 44 …”
Section: Resultsmentioning
confidence: 93%
“…Compared with antibacterial activity, modified fabrics have no activity against fungal strains, except Co-PTH-C, Ni-PTH-C, and Cd-PTH-C, which showed antifungal activities Figures 8 and 9. The outstanding antimicrobial activity of the metal-PTH-C over those of the ligand can be explained by the overtone concept and chelation theory [35]. Due to the overlap of the ligand orbital and the partial sharing of the positive charge of the metal ion with the donor groups, chelation will result in a greater reduction in the polarity of the metal ion [36].…”
Section: Antimicrobial Activitymentioning
confidence: 99%